Case report: First report of Legionella pneumophila and Bordetella bronchiseptica coinfection in an immunocompromised patient - La Sorda, Marilena; Palucci, Ivana; Natalini, Daniele; Fillo, Silvia; Giordani, Francesco; Paglione, Francesco; Monte, Anella; Lista, Florigio; Mancini, Fabiola; Girolamo, Antonietta; Rota, Maria Cristina; Caporali, Maria Grazia; et al. (Frontiers in Medicine, 2024)
Legionnaires' disease (LD) is a severe pneumonia, typically acquired by susceptible people through inhalation of aerosols contaminated by Legionella pneumophila (Lp). In this report, the first case of coinfection Lp-Bordetella bronchiseptica (Bb) is described. A possible source of Lp infection could be a hotel in Paris (France), where the patient had stayed before having symptoms. The Bb infection may have been transmitted from the dog, with which he was constantly in contact, although this has not been proven.